The Effect of Audiovisual-Based Education Media on Self Management in Type 2 Diabetes Mellitus Patients in the Work Area of UPT Puskesmas Ledeng - Susy Puspasari; Elah Eliawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: One of the management of diabetes mellitus type 2 is education. The provision of effective education is supported by the use of media that is attractive and more easily accepted by patients, one of which is using audiovisual media that contains elements of sound and images. Purpose: This study aims to determine the existence of the effect of audiovisual-based educational media on self-management in Type 2 Diabetes Mellitus patients in the working area of UPT Puskesmas Ledeng. Methods: This study is a quantitative study using a Quasi Experimental Two Group Pre-posttest Design where in this study there were an intervention group and a control group with 38 respondents. This research uses purposive sampling. Analysis using Paired Sample T-test and ANCOVA. The questionnaire used in this study was a demographic data questionnaire and Diabetes Self-management Questionnaire (DSMQ). Results: The results of the study on demographic data of respondents 71.1% were female, the average age of respondent was 50.82 years old with a standard deviation (SD) = 6.345, the education level attained by respondents were Primary School 55.3%, 50.0% working as housewife, with a duration of illness 3.21 years, and 60.5% of respondents had received previous information about type 2 diabetes mellitus. The results of the study in the control group a p value =0,586 > 0,05, the intervention group a p value =0,039 < 0,05. There is a significant influence between the audiovisual-based education on self-management of patients with type 2 diabetes mellitus. Conclusion: Nurses can provide audiovisual-based education as a medium of information and approaches in increasing knowledge and self-management behavior so as to avoid complications.